Архітектоніка образу князя Данила Галицького у «Галицько-Волинському літописі» - Адамович, Анастасія Євгенівна; Адамович, Анастасия Евгеньевна; Adamovych, Anastasiia; Шлєіна, Людмила Іванівна; Шлеина, Людмила Ивановна; Shlieina, Liudmyla (My University, 2016)
UK: У статті досліджуються особливості змалювання художнього образу Данила Галицького. Об’єктом даної роз- відки є генезис образу князя, його архітектоніка в «Галицько-Волинському літописі»; предметом – змістова організація та формотворчі прийоми зображення образу Данила Галицького. EN: The period of literary life which will be discussed, is one of little known ones. It is considered to be the time of spiritual decline and the reason was the Tatar-Mongol invasion of the thirteenth century. The scientists agreed that many papers of that period had moralistic character and were aimed the subjugation of the population and the authorities of the church rulers. Since the through image is a steady rate of people thinking in a certain period of time. As a historical figure the Prince was placed in the center of Galicia-Volyn Chronicle presentation in the middle of the thirteenth century. The author had made a significant step towards the new understanding of the nature and this probably made the record closer to the historical texts of the seventeenth century than even in sixteenth one. The article draws attention to the structure of the artistic image that consists of sensory images and ideas which follow them. The Prince mental qualities, moral, philosophical, ideological believes as well as the circumstances of their formation were analyzed from this point. The image content organization is embodied by means of forming methods. In this book they are psychological analysis, direct author characteristics, description by other characters, comparison with their images, showing environment, which to some extent affected the development of the psychological portrait of the Prince. RU: В статье исследуются особенности отображения художественного образа Данила Галицкого. Объектом данного исследования является генезис образа князя и его архитектоника в «Галицко-Волынской летописи»; предметом – смысловая организация и форма создания образа Данила Галицкого.
Рrince daniel of galicia image architectonic in galician-volynian chronicle
Архитектоника образа князя Данила Галицкого в «Галицко-Волынской летописи»
Keywords: психологічний портрет; чуттєвий образ; ідея; формотворчі прийоми; psychological portrait; sensual image; idea; forming methods; психологический портрет; чувственный образ; идея; формообразующие приемы